2001
DOI: 10.1183/09031936.01.00072401
|View full text |Cite
|
Sign up to set email alerts
|

Influence of setting on unattended respiratory monitoring in the sleep apnoea/hypopnoea syndrome

Abstract: The high demand for full polysomnography and the better quality of sleep at home are the main reasons for performing home sleep studies. Home respiratory monitoring has been evaluated in several studies, but the influence of setting on the results of unattended respiratory monitoring has not been assessed to date.Unattended monitoring of respiratory variables at home and in the sleep laboratory was conducted in 35 consecutive patients with suspected sleep apnoea/hypopnoea syndrome. Respiratory variables during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
(40 reference statements)
0
13
1
1
Order By: Relevance
“…With regard to the diagnosis of OSA, although the PSG is the gold standard, 1 over the last decade it has widely been demonstrated that home portable monitoring is a valid and reliable test. 16,17 Furthermore, recently, the Portable Monitoring Task Force of the American Academy of Sleep Medicine recommended that portable monitoring should be limited to subjects with a high risk for moderate to severe OSA, 18 such as in our work. In agreement with the literature, 19 3% of the home portable monitoring was not reliable, with no significant differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the diagnosis of OSA, although the PSG is the gold standard, 1 over the last decade it has widely been demonstrated that home portable monitoring is a valid and reliable test. 16,17 Furthermore, recently, the Portable Monitoring Task Force of the American Academy of Sleep Medicine recommended that portable monitoring should be limited to subjects with a high risk for moderate to severe OSA, 18 such as in our work. In agreement with the literature, 19 3% of the home portable monitoring was not reliable, with no significant differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previously validated non-attended respiratory polygraphy was performed at the patients' homes with a Somnea polygraph (Compumedics, Abbotsford, Australia) [21,22]. Studies without 5 h of correct signal recording were ruled out and repeated.…”
Section: Measurement Of Respiratory Function Data and Laboratory Assementioning
confidence: 99%
“…The diagnosis of OSAS using a simplified methodology in the home has been shown to be valid [13][14][15]. Although the PSG continues to be the gold standard for diagnosis [11], unsupervised ambulatory RP is accepted in patients with a high probability of OSAS [39].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory polygraphy (RP) is a cheaper and more accessible test and correlates well with PSG [13][14][15]. Home-based diagnostic strategies based on simple automated evaluation and treatment systems have also been proposed [16].…”
mentioning
confidence: 99%